MAQĀṢID AL-SHARĪ‘AH AND COPYRIGHT PROTECTION: A CRITICAL EXAMINATION OF COPYRIGHT REGULATION IN INDONESIA (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2025)
This article examines the integration of Maqāṣid al-Sharī‘ah as a theoretical framework in the protection of Intellectual Property Rights (IPR), with particular reference to copyright, focusing on the alignment between Islamic Sharī‘ah values and Law No. 28 of 2014 on Copyright (the Copyright Act) in Indonesia. The central issue identified is the imbalance between the Western utilitarian approach to IPR, which prioritises individual rights, and the principle of collective maṣlaḥah in Maqāṣid al-Sharī‘ah, which often neglects ethical and communal dimensions such as the prevention of maḍarrah and the redistribution of wealth through zakat on intellectual property. This imbalance has contributed to weak law enforcement in the digital era and restricted public access to knowledge. The research adopts a normative legal methodology, employing both a statute-based and a conceptual approach. The analysis highlights the strengths of the Copyright Act in supporting ḥifẓ al-māl and ḥifẓ al-‘aql through the economic and moral rights of authors, as well as its fair use exceptions, which correspond with the principle of general maṣlaḥah. However, it also identifies weaknesses, including inadequate implementation, long-term monopolies, and insufficient integration of communal values, all of which conflict with the objectives of Sharī‘ah in promoting holistic welfare. The article concludes that Maqāṣid al-Sharī‘ah can strengthen the protection of IPR by recommending amendments to the Copyright Act, including the incorporation of zakat on intellectual property, the reinforcement of Collective Management Organisations, and the promotion of ethical education within society. These measures would contribute to the realisation of falāḥ both temporal and spiritual through a balanced approach to innovation, justice, and social welfare in Indonesia.